Pattern of Maxillofacial Injuries during COVID-19 Pandemic at Birat Medical College Teaching Hospital of Eastern Nepal - Gurung, Gopal; Chapagain, Laxmi Prasad; Pokharel, Mona; Thapa, Sabana; Parajuli, Surya Bahadur (Birat Journal of Health Sciences, 2020)
Introduction: Maxillofacial injuries are one of the most common injuries seen in trauma patients. Road traffic accidents (RTA) are the most common cause of maxillofacial injuries all over the world. RTA are supposed to decrease due to lockdown which has become a usual phenomenon during the COVID- 19 pandemic. Changes in the etiology of maxillofacial injuries are supposed to dictate their pattern as well.Objectives: The objective of this study was to assess the pattern of maxillofacial injuries during the COVID-19 Pandemic at Birat Medical College and Teaching Hospital.Methodology: A cross-sectional study was conducted among the patients attending Birat Medical College and Teaching Hospital for the treatment of maxillofacial injuries from 1 May to 31 July 2020. Consecutive sampling was used to collect data from 52 study participants.Results: A total of 52 patients with maxillofacial injuries were studied. The age of patients ranged from 1 year to 73 years with a median age of 26 years. There were 69.2% (n=36) males with a male to female ratio of 2.25:1. The most common etiology was Road Traffic Accidents (50%, n=26). Laceration (70.7%, n=29) was the most common soft tissue injury. Parasymphysis fracture (23.8%, n=5) was the most common site of mandible fracture. The most common midface fracture was the zygomaticomaxillary complex (ZMC) fracture (40.9%, n=9).Conclusion: RTA still remains the most common etiology of maxillofacial injuries in spite of COVID-19 and the pattern of maxillofacial injuries has not changed much either.